2012
DOI: 10.1002/mrc.3895
|View full text |Cite
|
Sign up to set email alerts
|

New strategy for RDC‐assisted diastereotopic proton assignment using a combination of J‐scaled BIRD HSQC and J‐scaled BIRD HMQC/HSQC

Abstract: A new strategy to assign diastereotopic protons was developed on the basis of residual dipolar couplings (RDCs) collected in compressed poly(methyl methacrylate) (PMMA) gels. A combination of 2D J-scaled BIRD HSQC and J-scaled BIRD HMQC/HSQC NMR experiments was used to collect the RDC data. In the proposed strategy, the first experiment is used to measure (1)D(CH) for methine groups, the sum of (1)D(CHa) + (1)D(CHb) for methylene groups and the average (1)D(CH3) value for methyl groups. In turn, the small mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 20 publications
4
24
0
Order By: Relevance
“…Although organic compounds under isotropic conditions present a narrower range of J values, these intervals are commonly found when measuring J splittings in anisotropic conditions. For instance, it has been reported that experimental 2 T(HH) ( 2 J(HH) + 2 D(HH)) coupling values up to 30–40 Hz in magnitude and 1 T(CH) ( 1 J(CH) + 1 D(CH)) in the range of 100–180 Hz are measured in the case of strychnine dissolved in a CDCl 3 /poly‐methylmethacrylate gel …”
Section: Resultsmentioning
confidence: 99%
“…Although organic compounds under isotropic conditions present a narrower range of J values, these intervals are commonly found when measuring J splittings in anisotropic conditions. For instance, it has been reported that experimental 2 T(HH) ( 2 J(HH) + 2 D(HH)) coupling values up to 30–40 Hz in magnitude and 1 T(CH) ( 1 J(CH) + 1 D(CH)) in the range of 100–180 Hz are measured in the case of strychnine dissolved in a CDCl 3 /poly‐methylmethacrylate gel …”
Section: Resultsmentioning
confidence: 99%
“…A total of 32 2 J CH and 47 3 J CH unsigned coupling constants were extracted for a sample of strychnine in CDCl 3 from a single IPAP‐PIP‐HSQMBC experiment processed to yield α and β subspectra . The assignment was taken from previously published work . Most coupling constants could be determined with high precision compared to the accuracy of the DFT calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, the determination of the tiny 1 D (CH) of +0.3 Hz in H‐22 due to the very similar 1 J (C22‐H22) and 1 T (C22‐H22) values is only feasible due to its observable Δδ( 13 C) of +6.7 Hz. As recently reported, 1 J CH and 1 T CH measurements could also be performed along the indirect F1 dimension of complementary J CH ‐resolved HSQC ( J ‐HSQC) spectra . Figure A and 5B compare the SA‐PIP‐HSQC and J ‐HSQC cross‐peaks for the H13 and H15b protons, respectively, of 1 .…”
Section: Correlation Between Nmr Experiments and Isotropic/anisotropimentioning
confidence: 99%